ApoM maintains cellular homeostasis between mitophagy and apoptosis by affecting the stability of Nnt mRNA through the Zic3-ApoM-Elavl2-Nnt axis during neural tube closure - Qing Liu; Dan Liu; Yuejiao Wang; Xiaowei Wei; Wei Ma; Hui Gu; Shanshan Jia; Yiwen He; Wenting Luo; Songying Cao; Zhonghua Yang; Anhua Wu; et al. (Cell Death and Disease)
Abstract Research on the aetiology of neural tube defects (NTDs) has made progress in recent years. However, the molecular mechanism of apolipoproteins underlying NTDs development remains unclear. This study aimed to investigate the function of apolipoprotein M (ApoM) in the pathogenesis of NTDs and its underlying mechanisms. We demonstrated that ApoM expression was reduced in the spinal cord samples of rat models and human fetuses with NTDs respectively. Specifically, lack of ApoM resulted in reduced cytosolic localization of Elavl2 and caused Nnt mRNA degradation, which further led to impaired cell homeostasis by suppressing PINK1-PRKN-mediated mitophagy and promoting apoptosis and subsequent NTDs formation. Moreover, Zic3 directly interacted with the promoter of ApoM and activated its transcription. Lastly, intra-amniotic delivery of adenoviral recombinant Zic3 or ApoM could promote mitophagy and alleviate apoptosis in spinal cords of NTDs. Collectively, these findings highlight the important role of the Zic3-ApoM-Elavl2-Nnt axis in cellular homeostasis during neural tube development, thereby revealing an intracellular molecular regulatory mechanism of ApoM, providing a mechanistic basis for understanding embryonic neural development, and offering experimental evidence for potential therapeutic targets for NTDs.